Meningkatkan Konsentrasi pada Anak Usia 5 - 6 Tahun melalui Metode Bercerita di TK. Paud Istiqomah, Tanah Seribu, Binjai Selatan - Nadia Ariqah; Nurussakinah Daulay; Enny Nazrah Pulungan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine whether the storytelling method can improve the concentration of children aged 5-6 years at Paud Istiqomah, Tanah Seribu, South Binjai. This type of research is classroom action research (CAR) which is carried out in 2 cycles. Where each cycle is carried out 2 meetings. In each cycle, it is carried out through 4 stages, namely planning, implementation, observation, and reflection. The data collection tool used is observation. The subjects of the study were 12 children in Ismail class at Paud Istoqomah South Binjai, consisting of 6 girls and 6 boys. While the object of this study is Improving the Concentration of Children Aged 5-6 Years Through the Use of the Storytelling Method at Paud Istiqomah South Binjai The results of the analysis at meeting 1 cycle I after the storytelling method was carried out, the average assessment of children's concentration was 32.3% which means it is included in the sufficient category. While at meeting 2 cycle I after the storytelling method was carried out, the average concentration of children was 43.5%, still in the sufficient category. The results of observations and reflections at meeting 1 of cycle II after the storytelling method was carried out, the average assessment of children's concentration was 65.7%, which means it is included in the good category. While at meeting 2 of cycle II after the storytelling method was carried out, the average concentration of children increased to 80.5%, which is still included in the good category. From the results of the study above, it can be concluded that using the storytelling method can increase the concentration of children aged 5-6 years at Paud Istiqomah South Binjai.